The Physical, Mechanical, Barrier Characteristics, and Application of Edible Film from Yellow Sweet Potato and Aloe Vera Gel - Warkoyo Warkoyo; Maghfira Alvarizma Haris; Vritta Amroini Wahyudi (agriTECH, 2022)
This study aimed to determine the effect of the concentrations of yellow sweet potato starch and aloe vera gel on the physical, mechanical, and barrier characteristics of the edible film, which is applied as packaging for strawberries. It was carried out using a factorial randomized block design (RBD) consisting of 2 stages where the first step was making edible with varied yellow sweet potato starch  and aloe vera gel, followed by the application of the selected edible film. The two factors used as edible films were yellow sweet potato starch (Ipomea batatas) at 2%, 3%, and 4% w/v, as well as aloe vera gel (Aloevera barbadensis) at 5%, 10%, and 15% v/v concentrations. The formulation was applied to the strawberries to examine their ability to extend shelf life. The parameters tested in the first step were thickness, color, solubility, transparency, tensile strength, elongation, and WVTR, while weight loss, texture, and color were examined in the second stage for four days of storage. The results showed an interaction between yellow sweet potato starch and aloe vera gel on thickness with a range of 0.07-0.16 mm, L value of 66.73-73.23, a* value  of 0.8-2.5, b* value of 11.1-14.4, solubility  of 33.24-56.16%, transparency 2.68-3.43 A/mm, tensile strength 0.08-0.70 MPa, elongation in the range of 10.95-51.14%, and WVTR of 3.97-4.90 g/m 2 /24 hours. This showed that the application of edible coating with the best treatment can prevent a decrease in weight loss, texture andcolor intensity as well as extend the shelf life of strawberries up to two times.